Canadian democracy - Brooks, Stephen (Oxford University Press, 2020)
"What is the state of democracy in Canada? This is the central question of Stephen Brooks’s best-selling introduction to Canadian politics textbook, Canadian Democracy. In this revised ninth edition, Brooks continues to explore the characteristics and controversies associated with Canadian politics. He begins by addressing the social and economic contexts of the country’s politics before covering the basic elements and structures of government (e.g., the constitution, federalism, and the administrative state), political participation, and the current issues and challenges in Canadian political life. Highlights of this revised edition include: comprehensive updates throughout to bring readers the latest data, research, and analysis of current events; additional coverage of such topics as multiculturalism and interculturalism in Quebec, current trends in political communication, and Canadian foreign policy. This edition features a revised ancillary suite for students and instructors that includes podcasts, a test generator, an instructor’s manual, PowerPoint slides, and a student study guide. The ninth edition of Canadian Democracy is also available with an e-version of the textbook, flashcards of key terms and definitions, the Constitution Acts, 1867 & 1982 (including the Charter of Rights and Freedoms), and simulation activities that speak to Canadian politics, governance, and institutions."– Provided by publisher.